Proportion and factor associated with treatment default among tuberculosis patients in Sabah for the year 2016 -2020 - Zulkifly, Zahid (2023)
Background: TB, an airborne communicable disease, continues to pose a significant threat in our community and is the primary focus of concern for public health. Despite being preventable and curable, TB remains the second leading infectious cause of death after COVID-19, ranking 13th among all causes of mortality. According to data from the WHO Global Tuberculosis Report, TB claimed the lives of 1.6 million individuals in 2021. A significant challenge in managing tuberculosis (TB) is the inability to successfully complete the extended treatment duration, which typically lasts for six months or more. The persistence of the infection source contributes to heightened mortality rates, increased relapse rates, and facilitates the emergence of drug-resistant strains. Objective: This study aims to determine the proportion of treatment default, describe and determine sociodemographic, underlying disease, clinical characteristic and lifestyle factor associated with treatment default among tuberculosis patients in Sabah from year 2016 - 2020 Methodology: A case control study was carried out in March 2023 using secondary data. Eligible cases (treatment default) and control (treatment success) were selected through simple random sampling. The data was sourced from the National TB Registry, MyTB. Collection of data involved the use of a proforma form, which was later analysed using SPSS software. The association between treatment default and various factors, such as socio-demographic indicators, lifestyle, comorbidities, and clinical characteristics, was examined and analysed using simple and multiple logistic regression. Result: The proportion of treatment default among TB patients in Sabah from 2016 - 2020 was 3.13%. A total of 380 patients (190 cases and 190 controls) were selected in the study. Among cases group, majority of them were male (77.4%), local Sabahan (74.2%), Malaysian citizen (86.3%), lived in rural area (63.2%), received secondary education as highest education level (41.6%), non-diabetic (96.8%), HIV negative (98.4%), smoker (55.8%), diagnosed with pulmonary tuberculosis (93.7%), initial smear positive sputum AFB (73.7%), had minimal chest x-ray lesion (44.7%). Citizenship status (non-Malaysian citizen) and smoking status (smoker) and showed a significant association with TB treatment default (aOR 0.423; 95% CI: 0.248, 0.719), and (aOR 2.268; 95% CI: 1.492, 3.448) respectively. Conclusion: Based on these findings, we reached the conclusion that default in treatment was linked to non-Malaysian citizen status and smoking.